2004
DOI: 10.1291/hypres.27.877
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Antagonist Reduces Oxidative Stress by Upregulating Cu/Zn Superoxide Dismutase in Stroke-Prone Spontaneously Hypertensive Rats

Abstract: Recent studies have suggested that the calcium antagonists have an antiatherogenic antioxidant property.The effects of the calcium antagonists on reactive oxygen species (ROS)-related enzymes, however, remain unknown. We hypothesized that the calcium antagonists inhibit oxidative stress in the hearts of strokeprone spontaneously hypertensive rats (SHRSP) through the ROS-scavenging enzymes known as superoxide dismutases (SODs). Male 12-week-old Wister-Kyoto rats (WKY) and SHRSP were used for the study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
56
3

Year Published

2006
2006
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 35 publications
6
56
3
Order By: Relevance
“…This hypothesis is supported by recent experiments performed using the vascular tissue of stroke-prone SHR (44,45), in which the inhibition of angiotensin receptors or the angiotensin-converting enzyme system reduced ROS production. Our results are also consistent with investigations showing that cardioprotective treatments are mediated by a restoration or up-regulation of antioxidant enzymes (42,45). It is recognized that an increase in collagen concentration is an integral part of the extracellular matrix remodeling that takes place in the LVs during the natural aging process (66) and as well as in response to a variety of pathologies resulting in hypertrophy of this chamber (67,68).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This hypothesis is supported by recent experiments performed using the vascular tissue of stroke-prone SHR (44,45), in which the inhibition of angiotensin receptors or the angiotensin-converting enzyme system reduced ROS production. Our results are also consistent with investigations showing that cardioprotective treatments are mediated by a restoration or up-regulation of antioxidant enzymes (42,45). It is recognized that an increase in collagen concentration is an integral part of the extracellular matrix remodeling that takes place in the LVs during the natural aging process (66) and as well as in response to a variety of pathologies resulting in hypertrophy of this chamber (67,68).…”
Section: Discussionsupporting
confidence: 91%
“…The fact that hypertension improves with antioxidant therapy implies that oxidative stress is involved in that pathology (41). Recent investigations using hypertensive models other than SHR have shown that a decrease in oxidative stress is one of the mechanisms responsible for the efficacy of anti- hypertensive treatments such as calcium antagonists (42,43), angiotensin II type 1 receptor antagonists, or angiotensin-converting enzyme inhibitors (44,45).…”
Section: Discussionmentioning
confidence: 99%
“…The increase of ROS generation is also observed in cardiomyocytes or spleen cells by treatment with Ca 2+ ionophore A23187 (Przygodzki et al, 2005) or thapsigargin (Yip et al, 2005), respectively. In addition, antioxidant properties of Ca 2+ channel blockers have been observed with in vivo and in vitro studies (Buyukokuroglu et al, 2001;Umemoto et al, 2004;Ysunari et al, 2005). The molecular mechanism by which the increased Ca 2+ level promotes ROS production is not clearly understood.…”
Section: Discussionmentioning
confidence: 99%
“…These cellular actions by amlodipine would inhibit vascular remodeling (10,15). We recently reported that both enalapril and amlodipine might have additional benefits for the reduction of oxidative stress, vascular remodeling, and cardiac fibrosis in SHRSP hearts beyond blood-pressure lowering, and that amlodipine inhibited vascular remodeling of intramyocardial arteries in SHRSP by efficiently modifying Cu/Zn superoxide dismutase, more so than did enalapril (13). Amlodipine may also have antioxidant properties in addition to antihypertensive activity to inhibit neuronal cell death (21), which would be useful to prevent cerebrovascular accidents in hypertensive patients.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, recent clinical studies have revealed that the long-acting Ltype dihydropyridine calcium antagonist amlodipine may have antiatherogenic properties independent of its effects on vasodilatation (10)(11)(12). We have also shown that amlodipine may have antiatherosclerotic antioxidative action beyond blood-pressure lowering in stroke-prone spontaneously hypertensive rat (SHRSP) hearts (13). However, the precise mechanisms regulating vascular SMC phenotypic modulation and the critical signal transductions affecting the vascular SMC phenotype in hypertension by amlodipine remain unclear in vivo.…”
Section: Introductionmentioning
confidence: 99%